PHYSICO-CHEMICAL ANALYSIS AND EVALUATION OF ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF KITMARDO RASA (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda as an ancient science developed through trials, experiments, and observations. Ayurveda has been honored and applied for the prevention and cure of human ailments with purity and sacredness. Ayurvedic medicines have proven to be effective in treating various diseases using metallic, non-metallic, and compound materials. The segment of RASASHASTRA focuses on inorganic pharmaceutical preparations, which require the process of SHODHANA to make toxic raw materials safe for consumption. Different types of Shodhana techniques are described in RASAGRANTHAS to convert raw materials into effective medicinal formulations. Techniques like Marana, Parpati Kalpana, KupipakwaRasaayans, and Kharlya Kalpana are used to prepare medicines based on ancient Granthas for curing ailments. The field of RASASHASTRA deals with mercury, minerals, metals, and aquatic substances categorized based on their actions on Dhatu and the body. Kajjali, a combination of Parada and Gandhaka, is widely used in formulations and has therapeutic applications on its own. Kajjali is indicated for various conditions like Visarpa, Vidhradhi, Charmadal, Kandu, Pama, and Upadandha, which are correlated with infectious diseases. The abstract also emphasizes the need to find new antimicrobial compounds due to the development of antibiotic-resistant bacteria. Ayurvedic herbo-mineral preparations are suggested as potential sources for antimicrobial activity evaluation. The Kitmardo Rasa, a combination of various ingredients, is discussed as a Karliya Kalpana formulation, and the study aims to evaluate its physico-chemical properties and antibacterial/antifungal activity in vitro.